(untitled) - Wilkinson, Christina (Mentor, Ohio, 2003)
Bicentennial Barns of Ohio captures the essence of the Bicentennial Barn-painting project by weaving a tapestry of heartwarming marratives. In the fall of 2002. Ohio author Christina Wilkinson personally visited all eighty-eight countries in Ohio, photographing the barns and former owners.
Keywords: Barns,Ohio,Logos ( Symbols ),Ohio; History, local,Lịch sử, địa phương; Ohio,Ohio